An Ni–PyBisulidine complex for the asymmetric hydrophosphonylation of aldehydes. Issue 39 (20th September 2016) - Zeng, Youmao; Deng, Ping; Zhang, Shixiong; Yan, Hong; Liang, Guojuan; Xiong, Yan; Zhou, Hui
Abstract : A novel Ni–PyBisulidine complex has been developed for the asymmetric hydrophosphonylation of aldehydes. Abstract : A novel Ni–PyBisulidine complex has been developed for the asymmetric hydrophosphonylation of aldehydes. A variety of aromatic, heteroaromatic, condensed-ring, α, β-unsaturated, and aliphatic aldehydes are found to be suitable substrates for the reaction, and the desired α-hydroxy phosphonates are obtained in up to 99% yield and 97% ee.